Antimicrobial Resistant Staphylococcus spp., Escherichia coli, and Salmonella spp. in Food Handlers: A Global Review of Persistence, Transmission, and Mitigation Challenges - Gustavo Guimarães Fernandes Viana; Marita Vedovelli Cardozo; Juliano Gonçalves Pereira; Gabriel Augusto Marques Rossi (Pathogens)
Antimicrobial resistance in foodborne pathogens represents a critical global health challenge, with food handlers serving as key contributors in their transmission. This comprehensive review synthesizes evidence on the prevalence, transmission dynamics, and antimicrobial resistance patterns of three major pathogens, Staphylococcus spp., Escherichia coli, and Salmonella spp., among food handlers worldwide. Analysis of studies across diverse geographical regions reveals considerable variation in colonization rates, with Staphylococcus spp. prevalence ranging from 19.5% to 95.0%, Escherichia coli from 2.8% to 89.3%, and Salmonella spp. from 0.07% to 9.1%. Resistance profiles demonstrate alarming trends, including widespread β-lactam resistance and emerging resistance to last-resort antibiotics like carbapenems. Particularly concerning is the high occurrence of multidrug resistant (MDR) strains and extended spectrum β-lactamase (ESBL) producers in low- and middle-income countries. This review identified inadequate handwashing, poor hygiene infrastructure, and asymptomatic carriage as critical factors facilitating the transmission of antimicrobial resistant strains. These findings underscore the urgent need for enhanced surveillance systems, targeted decolonization strategies, improved hygiene protocols, and food handler education to mitigate the spread of resistant pathogens through the food chain.